(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In this scientific study, the ability to modify the surface using nanosecond 1064 nm fiber laser by controlling the speed and scanning line step in the marking process was demonstrated. An experimental matrix for laser marking was developed, consisting of 8 columns for marking line step and 5 rows for marking speed. The laser marked surfaces were measured using a laser scanning microscope and compared with the surface as supplied. From the obtained deviations of roughness Ra, Rz and Rq as a function of marking speed and marking line step, graphical dependencies were constructed for comparative analysis. The modified roughness is also compared with the roughness as supplied. Within this research the effect of laser treatment on the hydrophilicity/hydrophobicity of the surface was studied as well. Plots of dependences of the contact angle CA, the marking line step Δx and the overlap coefficient Ksoc are plotted.